2005
DOI: 10.1186/1472-6963-5-63
|View full text |Cite
|
Sign up to set email alerts
|

Chances of late surgery in relation to length of wait lists

Abstract: BackgroundThe proportion of patients who undergo surgery within a clinically safe time is an important performance indicator in health systems that use wait lists to manage access to care. However, little is known about chances of on-time surgery according to variations in existing demand. We sought to determine what proportion of patients have had late coronary bypass surgery after registration on wait lists of different size in a network of hospitals with uniform standards for timing of surgery.MethodsUsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, admission for elective (i.e., non-emergency but necessary) surgery within the recommended time can be easily affected if surgical services experience an uneven influx of more urgent cases [ 9 ]. We previously performed an empirical analysis of a population-based registry and found that the length of the queue at the time of a patient's registration also affected the time to surgery [ 10 ], the probability of surgery being delayed [ 11 ], and the probability of death before planned surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, admission for elective (i.e., non-emergency but necessary) surgery within the recommended time can be easily affected if surgical services experience an uneven influx of more urgent cases [ 9 ]. We previously performed an empirical analysis of a population-based registry and found that the length of the queue at the time of a patient's registration also affected the time to surgery [ 10 ], the probability of surgery being delayed [ 11 ], and the probability of death before planned surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 For instance, waiting more than 6 months for a hip replacement has a significant impact on physical disability and psychosocial functioning. 14 Although the risk of surgery being overdue increases with longer waiting lists, 15 long waiting times are not necessarily clinically unsafe. Thus, waiting lists should always report the proportion of patients who undergo surgery outside of clinically safe and acceptable time limits because this would allow cases to be redistributed across hospitals to reduce the proportion of late surgeries.…”
Section: Waiting Time or Clinical Priority?mentioning
confidence: 99%